2011
DOI: 10.1093/mp/ssq063
|View full text |Cite
|
Sign up to set email alerts
|

Functions of Xyloglucan in Plant Cells

Abstract: While an increase in the number of xyloglucan tethers between the cellulose microfibrils in plant cell walls increases the walls' rigidity, the degradation of these tethers causes the walls to loosen. Degradation can occur either through the integration of xyloglucan oligosaccharides due to the action of xyloglucan endotransglucosylase or through direct hydrolysis due to the action of xyloglucanase. This is why the addition of xyloglucan and its fragment oligosaccharides causes plant tissue tension to increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
111
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 182 publications
(114 citation statements)
references
References 47 publications
1
111
0
2
Order By: Relevance
“…A lack of detectable xyloglucan in the xxt1/xxt2 double mutant in Arabidopsis caused a significant reduction in the stiffness and strength parameters of the mutants (Cavalier et al 2008). The xyloglucan acts as a tether in the extracellular matrix and plays a key role in the loosening and tightening of cellulose microfibrils (Hayashi and Kaida 2011). The SNP (PGWD1-0511) represents a synonymous substitution (TCA-TCG) coding for a serine.…”
Section: Resultsmentioning
confidence: 99%
“…A lack of detectable xyloglucan in the xxt1/xxt2 double mutant in Arabidopsis caused a significant reduction in the stiffness and strength parameters of the mutants (Cavalier et al 2008). The xyloglucan acts as a tether in the extracellular matrix and plays a key role in the loosening and tightening of cellulose microfibrils (Hayashi and Kaida 2011). The SNP (PGWD1-0511) represents a synonymous substitution (TCA-TCG) coding for a serine.…”
Section: Resultsmentioning
confidence: 99%
“…1E) showed that cells approaching the root surface become more elongated, and we thought that this could be effected by some nonpectin components. XyG is one of the main hemicelluloses implicated in cell wall extensibility and cell elongation (Scheller and Ulvskov, 2010;Hayashi and Kaida, 2011;Park and Cosgrove, 2015), and we localized XyG in pea roots using three mAbs recognizing distinct XyG structural features: LM24, Figure 7. Immunolocalization of XAG in the pea root apex.…”
Section: Xyg and Extensin Epitopes Display Polarized Distribution Witmentioning
confidence: 99%
“…This high relative amount of branched glucose and the presence of T-Fucp, T-Galp, T-Xylp, (1 → 2)-Galp, and (1 → 2)-Xylp residues allows to infer the presence of xyloglucans (Fry, 1988;Hayashi & Kaida, 2011;Hoffman et al, 2005).…”
Section: Glycosidic Linkage Analysismentioning
confidence: 99%